Analysis of the reasons for the regular practice of physical activity in the return of injuries of amateur Volleyball athletes - Ribeiro, Luciana Botelho; Tertuliano, Ivan Wallan; Rebustini, Flávio; Valim-Rogatto, Priscila Carneiro; Machado, Afonso Antonio (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Background: Motivation is an important variable for sports performance. It is important because it is a psychological variable that coordinates and directs the intensity and direction of the individuals’ efforts in the activity to be performed. In this way, studying it, as a variable that interferes in the performance of athletes is of paramount importance. Objective: To investigate the reasons of injured volleyball athletes to return to regular practice of their activities. Method: The research was carried out using an sequential exploratory, mixed method. IMPRAF-54 and the Focus Group technique were used. The Inventory of Motivation for the Regular Practice of Physical Activity (IMPRAF-54) evaluates the reasons for the practice of regular physical activity, distributed in six different processes. Thus, in the first phase, 32 amateur volleyball players of the juvenile and adult categories, of both genders, with a mean age of 35.45 years participated in the study. After the participants answered the questionnaire, the Focus group was formed with 10 athletes, who participated in the second part of the study. These athletes participated in four meetings to discuss the dimensions posed by the researchers, in an attempt to observe if the athletes interpreted the dimensions of IMPRAF-54 in ways similar to that expected by the instrument. Results: The results showed that athletes were motivated in the dimension of pleasure, health and sociability. In the Focus group, the results reinforced the data of the IMPRAF 54, in addition, this phase allowed to explore the perceptions of the sensations and the feelings of the athletes while injured. Conclusion: It is possible to state that while amateur athletes are recovering from injuries, the focus is not competition. Knowledge of these results may aid in the type of psychological work that can be performed while athletes are injured.